The impact of exposure to cartoons promoting healthy eating on children's food preferences and choices - Gonçalves, Sónia (2018)
Objective: This study explored whether a cartoon show with healthy eating messages positively affected children's food choices and food preferences.Design: Experimental between-subjects design.Setting: Four elementary schools in Portugal were investigated.Participants: Children (aged 4-8 years; n = 142) were randomly assigned to 1 of 2 groups: a comparison group (n = 73) was exposed to cartoons with no reference to food and an intervention group (n = 69) was exposed to cartoons with healthy eating messages. After viewing, each child was given the opportunity to eat ad libitum for 10 minutes from a small selection of snack foods.Main Outcome Measure: Number of healthy and unhealthy food items chosen. Food preferences were measured using an adapted version of the Leeds Food Preference Checklist.Analysis: Generalized linear models were used to test for differences between groups. Results were considered significant at P <= .05.Results: Children in the experimental group chose significantly more healthy food items than did those in the comparison group (B = -.600; SE = .19; P < .05).Conclusions and Implications: Future studies may address the effect of prolonged exposure to healthy eating cartoons. Cartoons can be used to promote healthy food choices and can be a part of health promotion campaigns.